2014
DOI: 10.4314/ejesm.v7i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Levels of Extension Agents and their Perceived Impact of Climate Change on Extension Service Provision in Ghana

Abstract: This study examined the knowledge levels of extension agents and their perceived impact of climate change on extension service provision in Ghana. Specifically, it examined awareness levels of agents on the causes, effects and methods for mitigating climate change. It also determined their perceived impact of climate on extension service delivery. A structured questionnaire was used to elicit information from a sample size of 192 respondents from 10 regions in Ghana who were randomly selected. The data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In the study of farmers' knowledge, it was found that they mostly had a low level of knowledge on climate change which is contrary to the results of Al Buloshi & Ramadan, 2015;Ogunlade et al, 2014;and Rodriguez-Franco & Haan, 2015; and is similar to the study of Kabir et al (2016) according to which, only 6.5% of farmers had a high level of climate change knowledge. The result of the study also indicated that knowledge had a significant relationship with the adaptive capacity of farmers.…”
Section: Discussionsupporting
confidence: 66%
“…In the study of farmers' knowledge, it was found that they mostly had a low level of knowledge on climate change which is contrary to the results of Al Buloshi & Ramadan, 2015;Ogunlade et al, 2014;and Rodriguez-Franco & Haan, 2015; and is similar to the study of Kabir et al (2016) according to which, only 6.5% of farmers had a high level of climate change knowledge. The result of the study also indicated that knowledge had a significant relationship with the adaptive capacity of farmers.…”
Section: Discussionsupporting
confidence: 66%
“…Although most of extension agents has excellent knowledge about climate change (Ogunlade, Abdulwahab & Mensah, 2014), a large number need training on climate change (Adisa and Balogun,2012;Onyeme and Iwuchukwu ,2012). Fish farming activities has seen a rapid increase in the number, area and production of fish farms.Fish farmers require periodic update and upgrading of their technical knowledge and skill, they need training to remove barriers, improve technical competency and efficiency for better resource utilization, increase productivity and performance (Ifejika, Uzokwe & Oladosu,2013) .…”
Section: Characteristics Of Extension Agentsmentioning
confidence: 99%
“…Other African countries have also noticed this trend (Antwi-Agyei & Stringer, 2021;Zafezeka, et. al., 2019;Ogunlade, et. al., 2014).…”
Section: Introductionmentioning
confidence: 99%